Selected biomarkers of oxidative stress in healthy Beagle dogs: A preliminary study - Porato, Mathilde; Noël, Stéphanie; Pincemail, Joël; Albert, Adelin; Cheramy-Bien, Jean-Paul; Le Goff, Caroline; Hamaide, Annick (Frontiers in Veterinary Science, 2023)
While oxidative stress has been studied in pathologic conditions in dogs, data in presumably healthy dogs and standardized protocols are lacking. This work purposed to bridge the gap by presenting provisional physiological ranges for oxidative stress biomarkers in a group of Beagle dogs. Based on our long-standing clinical expertise in the field of oxidative stress, nine plasma biomarkers of oxidative stress were evaluated for their concentrations (mean ± SD) in 14 healthy adult Beagle dogs: vitamins C (7.90 ± 1.36 µg/mL) and E (34.1 ± 6.63 µg/mL), zinc (0.80 ± 0.17 mg/L), copper (0.54 ± 0.048 mg/L), selenium (256 ± 25.7 µg/L), total and oxidized glutathione (822 ± 108 µM and 3.56 ± 1.76 µM), myeloperoxidase 67.4 ± 56.2 ng/mL) and isoprostanes (340 ± 95.3 ng/mL). Glutathione peroxidase activity and superoxide anion production in whole blood were measured too. Glutathione peroxidase activity was 473 ± 34.0 UI/g of hemoglobin and superoxide anion production in whole blood was 18,930 ± 12,742 counts per 30 minutes. Reduced glutathione/oxidized glutathione and copper/zinc ratios were respectively 280 ± 139 and 0.70 ± 0.15. Sex-related differences were recorded for zinc (p = 0.0081), copper/zinc ratio (p = 0.0036) and plasma isoprostanes (p = 0.0045). Provisional physiological norms covering 95% of our group were proposed for each biomarker and should be of interest for future studies of canine oxidative stress.